Navigating the club-to-international transition process: An exploration of English Premier League youth footballers` experiences - Edwards, D.; Brannagan, P. M. (International Journal of Sports Science & Coaching, 2023)
This study investigated the experiences of youth footballers as they made their transition from club football to the England youth international football teams. The club-to-international transition focuses on the movement of an individual from club sport to international representation, a within-career transition that comes with its own specific demands, characterised by the dual stakeholders of club and national governing body. The authors completed semi-structured interviews with 11 current youth footballers to better understand the type of coaching support they were provided by both club and national team coaches before, during and after international representation. Through thematic analysis, it was found that there was ambiguity as to the support offered to youth international footballers, with players explaining that feedback provided post-training camp did not support them in their development. Players also suggested the importance of sharing performance data between the domains (club and international) as good practice that helped them to have a more successful transition. These novel results suggest that the transition into youth international football should be seen as an important step in the development of the young footballer, however, clubs and national governing bodies need to work closer together to use this transition as a developmental opportunity. Several practical applications are discussed, including the importance of key stakeholders clearly outlining their responsibilities to the player during international representation.